Improved performance of binder-free zeolite Y for low-temperature sorption heat storage. Issue 24 (5th June 2018) - Ristić, Alenka; Fischer, Fabian; Hauer, Andreas; Zabukovec Logar, Nataša
Abstract : Improved performance of modified binder-free zeolite Y in mobile sorption heat storage for low-temperature industrial waste heat recovery. Abstract : The sustainable generation of energy and low-energy consuming technologies are two main approaches to combat climate change and reduce carbon dioxide emissions. Sorption heat storage is part of the second approach. Therefore, adsorbents that achieve high energy storage density under the working conditions of the storage application are required. In this study, the hydrophilic properties of a granulated binder-free zeolite NaY were tailored with the aim of increasing its performance at a desorption temperature of 140 °C for mobile sorption heat storage. Top-down approaches, such as chemical treatment with the chelating agent H4 EDTA, treatment with the inorganic acid HCl and sequential ion exchange with acid treatment, were used in order to decrease the desorption temperature and optimize the low-temperature heat storage density. All the modified samples showed a decrease in the desorption temperature from 10 to 30 °C compared to the parent sample; only the desorption temperature of the acid-treated Mg-exchanged NaY sample increased. The effect of different treatments on the structural properties of the materials, including the generation of framework defects and mesoporosity was determined. The energy storage densities of the NaY and all the modified samples are considerably higher in comparison to the currently used adsorbent (NaMSX) in mobile sorption heat storage for low-temperature industrial waste heat recovery.